Selection of Probiotics for Honey Bees: The In Vitro Inhibition of Paenibacillus larvae, Melissococcus plutonius, and Serratia marcescens Strain Sicaria by Host-Specific Lactobacilli and Bifidobacteria - Buse Dengiz; Jiří Killer; Jaroslav Havlík; Pavel Dobeš; Pavel Hyršl (Microorganisms)
Host-specific Lactobacillus and Bifidobacterium species constitute the core microbiota of the honey bee digestive tract and are recognized for their probiotic properties. One of the properties of these bacteria is the inhibition of bacterial pathogens such as Paenibacillus larvae and Melissococcus plutonius, the causative agents of American and European foulbrood, respectively. Additionally, Serratia marcescens has emerged as a relevant opportunistic pathogen. Although several previously published studies have examined the inhibition of selected bacterial pathogens of bees by members of the bee physiological microbiota, none have simultaneously investigated the inhibition of multiple clinical isolates of P. larvae, M. plutonius, and S. marcescens using a wide range of bifidobacterial and lactobacilli strains isolated from various locations within a single country. Thus, this study evaluated the antimicrobial potential of Lactobacillus and Bifidobacterium strains against these pathogens, with a focus on strain-dependent inhibition. A total of 111 bacterial strains (62 Lactobacillus and 49 Bifidobacterium) were isolated from the digestive tracts of honey bees collected from eight sites across the Czech Republic. Using 16S rRNA gene sequencing, the isolates were classified and tested in vitro against four P. larvae isolates, one M. plutonius isolate, and the S. marcescens strain sicaria in modified BHI medium. Twenty-eight strains (~26%) exhibited strong inhibition (≥21 mm) against at least two P. larvae isolates, while 12 strains showed moderate inhibition (16–20 mm) against all four isolates. Inhibition of M. plutonius and S. marcescens was observed in three and twenty strains, respectively. The most effective strains belonged to Bifidobacterium asteroides, B. choladohabitans, B. polysaccharolyticum, Lactobacillus apis, L. helsingborgensis, L. kullabergensis, and L. melliventris. These results underscore the strain-dependent nature of antimicrobial activity and highlight the importance of selecting probiotic strains with broad-spectrum pathogen inhibition to support honey bee health.